Kajian Literatur Pengembangan Biogas dari Fermentasi Anaerob di Indonesia (2016-2024) - Wahid Nuruddin , Abdul; Kalista, Anggia (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2025)
The production of biogas through anaerobic fermentation in Indonesia faces various technical, socio-economic, and policy-related challenges that hinder its efficiency and application as a sustainable energy source. This research aims to analyze the state of biogas production in Indonesia from 2016 to 2024, with focus on the technical, socio-economic aspect, and government policies that influence it. The study uses the Systematic Literature Review (SLR) method, utilizing Google Scholar to collect relevant articles. A total of 130 articles were selected based on inclusion and exclusion criteria, ensuring the relevance and consistency of the analyzed data. The finding in the study show that optimal conditions for technical aspect such as substrat use, maintaining a constant temperature of 350C, and pH 7 signifinacntly increase biogas production. This analysis also examines the importance of government incentives and public awareness in promoting the adoption of biogas. The study concludes that collaborative effort in optimizing technology, rising public awareness, and implementing supportive policies are crucial for biogas to play an importance role in Indonesia energy mix, ultimately contributing to sustainable renewable energy solutions. This study contributes to the existing body of knowledge by providing insights into the interactions between technology, socio-economic factors, and policy frameworks in biogas production, as well as offering a foundation for future research and its application in renewable energy.